2016
DOI: 10.1097/aog.0000000000001244
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy of Trichloroacetic Acid in the Treatment of Cervical Intraepithelial Neoplasia

Abstract: A high regression and remission rate and a high HPV clearance rate were observed 8 weeks after topical 85% trichloroacetic acid treatment for patients with CIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Photodynamic therapy using a topical hexyl-aminolevulinic acid (ALA) cream followed by the application of a light-emitting device by the patient herself, had only a limited effect [6,7]. Corrosive treatment of the cervical surface with topical 85% trichloroacetic acid in an outpatient setting showed promising results, but with not negligible vasovagal symptoms immediately after treatment [8]. Recently, an aqueous hydrocolloid vaginal gel was developed, containing highly dispersed silicon dioxide and DEFLAMIN® as active agents.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy using a topical hexyl-aminolevulinic acid (ALA) cream followed by the application of a light-emitting device by the patient herself, had only a limited effect [6,7]. Corrosive treatment of the cervical surface with topical 85% trichloroacetic acid in an outpatient setting showed promising results, but with not negligible vasovagal symptoms immediately after treatment [8]. Recently, an aqueous hydrocolloid vaginal gel was developed, containing highly dispersed silicon dioxide and DEFLAMIN® as active agents.…”
Section: Introductionmentioning
confidence: 99%
“…Computer aided data optimisation has been applied, at various levels of sophistication and automation in DC voltammetry, to relatively simple problems requiring the estimation of no more than about five parameters (see for example,,, and references cited therein). Typically in DC voltammetry with automated data optimisation, each experimental data set is interrogated using a particular simulation model and say four parameters such as E 0 , k 0 , α, and D (diffusion coefficient) in the case of a simple solution soluble electron transfer reaction as reported by Scharbert and Speiser .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, TCA has low viscosity; therefore, special attention is required because it can easily drip down onto normal tissue, which can also become chemically coagulated. Therefore, when managing CIN, the wooden stick end of the cotton swab saturated with trichloroacetic acid is carefully applied [1]. The TCA should be handled very carefully even when used in treatment at the medical office and also with care in drug placement and administration as a high hazard medicine.…”
Section: Discussionmentioning
confidence: 99%
“…for cervical intraepithelial neoplasia Geisler et al (2016). demonstrated that a high regression and remission rate and a high HPV clearance rate were observed 8 weeks after topical 85% trichloroacetic acid treatment for patients with CIN[1].However, numerous studies have been reported about the risk of chemical burn related TCA[2,3]. Ryu et al not-ed that Acetic acid (37%) was the most common cause of chemical burns treated in a single hospital study between 2000 and 2009, followed by Hydrofluoric acid (20%),…”
mentioning
confidence: 99%